Environmental control of interannual and seasonal variability in dinoflagellate cyst export flux over 18 years in the Cape Blanc upwelling region (Mauritania) - Roza, Surya Eldo V.; Versteegh, Gerard J. M.; Pospelova, Vera; Zonneveld, Karin A. F. (Frontiers in Marine Science, 2024)
The increasing threat of anthropogenic environment and climate change amplifies the urgency to investigate the effect of these changes on marine ecosystems. We provide information about the export flux of organic-walled dinoflagellate cysts between 2003 and 2020 in the upwelling ecosystem off Cape Blanc (Mauritania), one of the world's most productive regions. We compared the cyst export flux with variability in environmental parameters, such as wind speed, wind direction, dust emission, sea surface temperature (SST), SST difference between trap location and open ocean (SSTa), and chlorophyll-a concentration. This information is valuable to determine the ecological signal of dinoflagellate cysts that could be applied in recent and paleo records. The total export production of dinoflagellate cysts fluctuated between 0 - 1.18 x 10.5 cysts m-2 d-1 for the heterotrophs and 0 - 1.06 x 10 4 cysts m-2 d-1 for the photo-/mixotrophs. The export productions of both groups were in line with changes in upwelling intensity, which in most years, intensified in spring -summer. Dinoflagellate cyst association was dominated by heterotrophic taxa that formed an average of 94% of the association throughout the sediment trap record. A strong interannual variation in the cyst export fluxes, as well as the association composition was observed in the record. We identified five groups that showed comparable variability in export production with changes in environmental conditions: (1) maximal upwelling; Echinidinium delicatum/granulatum, E. transparantum/zonneveldiae, Echinidinium spp., Trinovantedinium spp., and Protoperidinium latidorsale, (2) combined maximal upwelling and dust input; Archaeperidinium spp., P. americanum, cysts of P. stellatum, and P. subinerme, (3) upwelling relaxation; Gymnodinium spp. and L. polyedra, (4) warm surface waters; Bitectatodinium spongium and Protoceratium reticulatum, (5) species with no specific relationship to the studied environmental variables; Brigantedinium spp., E. aculeatum, Impagidinium aculeatum, P. conicum, P. monospinum, Pentapharsodinium dalei, and Spiniferites spp. The sediment trap record documented a gradual shift in the cyst taxa association that co-occurred with the gradual increase of Saharan dust input to the region, notably after 2008. The cyst association contained five photo-/mixotrophic taxa that were formed by potentially toxic dinoflagellates. The latter could cause threats to the socio-economy of coastal communities.